Integrating educational technologies: critical analysis and perspectives from teacher training students - Tommaso Santilli; Silvia Ceccacci; Noemi Del Bianco; Ilaria D'Angelo; Catia Giaconi (Je-LKS: Journal of E-Learning and Knowledge Society)
The growing spread of Information and Communication Technologies (ICTs) across multiple contexts of use has triggered the transformation of traditional educational environments to welcome their use in ordinary teaching and learning processes. However, the mere availability and supply of educational technologies does not guarantee the activation of meaningful and inclusive trajectories for technology integration in the classroom, as the knowledge and competences of teachers and students is still the primary factor to drive an equitable and effective use of technology as a didactic mediator. Considering the challenges of teacher training within an ever-changing technological landscape, this paper focuses on the Italian national context, analysing the perceptions of 830 Italian teachers participating in a training course for teachers (30 credits Training, Prime Ministerial Decree of 4 August 2023) with reference to the use of ICTs in their previous teaching experience. The Italian version of the Intrapersonal Technology Integration Scale (ITIS) was implemented as a tool to collect data and examine the dynamic relationship between the teachers’ perceived competences on educational technologies and the factual use they make of them to support teaching across disciplines. Results show useful insights on the reasons underlying the choice of implementing and integrating technology in ordinary teaching practices and unveil possible trajectories to reshape the training paths for teachers. In this sense, this contribution unfolds a deeper analysis of the intersection between teacher professionalism, educational technologies and educational systems’ inclusiveness and efficacy.